Effectiveness of Cognitive-Behavioral Training on Reducing the Secondary Trauma Symptoms of PTSD Veterans\' Wives - Kh. Abolmaali; M. Aghaeepour Gavasaraee (Afarand Scholarly Publishing Institute, 2015)
Aims: Secondary trauma is a psychological consequence of direct and prolonged contact with a post-traumatic stress disorder person. The purpose of this study was to evaluate the efficacy of instruction of cognitive-behavioral techniques on reduction of secondary trauma symptoms in wives of post-traumatic stress disorder veterans, with controlling the effect of depression, anxiety and stress. Materials & Methods: In this quasi-experimental research with pretest-posttest with control group design, 22 spouses of post-traumatic stress disorder veterans referred to Sadr Psychiatric Hospital of Tehran, Iran in 2013 were studied. The people who have attained high score on the secondary trauma test were randomly assigned to two experimental and control groups. The research instruments were a demographic questionnaire, questionnaire of secondary post-traumatic stress, and questionnaire of depression, anxiety and stress. The experimental group was weekly taught cognitive-behavioral techniques in 13 sessions in 135 minutes. The analysis of data was performed by univariate and multivariate analysis of covariance. Findings: The mean of secondary trauma and components of intrusion, avoidance, and arousal in all cases in the experimental group were lower than the control group. Instruction of cognitive behavioral techniques with controlling the effect of depression, anxiety and stress was effective in reduction of secondary trauma symptoms in wives of post-traumatic stress disorder veterans (p<0.05). Conclusion: Teaching the cognitive-behavioral techniques is an effective strategy for reducing the symptoms of secondary traumatic stress.